Lao People's Democratic Republic : Technical Assistance Report-The Development of Risk-Based Supervision. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the main findings and recommendations made by the IMF Mission regarding the development of risk-based supervision (RBS) in the Lao People's Democratic Republic. Over the past few months, the Bank of Lao has made great strides in preparing for implementation of risk-based supervision of banks. A new supervisory manual reflecting key principles of risk-based approach to supervision has been drafted. The new draft template of the Report of Onsite Examination is broadly in line with the past technical assistance recommendations. Some improvements could support the analysis of trends over longer periods of time, and emphasize exceptions to prudential and/or regulatory norms. Planning an onsite examination using new RBS methods is a logical next step.